2003
DOI: 10.1159/000070672
|View full text |Cite
|
Sign up to set email alerts
|

MR Imaging of Arrhythmogenic Right Ventricular Cardiomyopathy: Morphologic Findings and Interobserver Reliability

Abstract: Background: Magnetic resonance (MR) imaging is frequently used to diagnose arrhythmogenic right ventricular cardiomyopathy/dysplasia (ARVC/D). However, the reliability of various MR imaging features for diagnosing ARVC/D is unknown. The purpose of this study was to determine which morphologic MR imaging features have the greatest interobserver reliability for diagnosing ARVC/D. Methods: Forty-five sets of films of cardiac MR images were sent to 8 radiologists and 5 cardiologists with experience in this field. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
112
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 182 publications
(116 citation statements)
references
References 14 publications
2
112
0
2
Order By: Relevance
“…Quantitative analysis showed that RV enddiastolic diameter and outflow tract area were significantly higher, and RV ejection fraction lower in ARVC/D patients compared to controls 66 . Using less dedicated software, the presence of fatty infiltration of the right ventricular myocardium may be less reliably detected 68 . Moreover, even in normal individuals epicardial fat is usually present and tongues of epicardial fat may extend into the RV myocardium 68 .…”
Section: Right Ventricular Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative analysis showed that RV enddiastolic diameter and outflow tract area were significantly higher, and RV ejection fraction lower in ARVC/D patients compared to controls 66 . Using less dedicated software, the presence of fatty infiltration of the right ventricular myocardium may be less reliably detected 68 . Moreover, even in normal individuals epicardial fat is usually present and tongues of epicardial fat may extend into the RV myocardium 68 .…”
Section: Right Ventricular Functionmentioning
confidence: 99%
“…Using less dedicated software, the presence of fatty infiltration of the right ventricular myocardium may be less reliably detected 68 . Moreover, even in normal individuals epicardial fat is usually present and tongues of epicardial fat may extend into the RV myocardium 68 . ARVC/D patients, but not normal individuals, have fibrosis of the RV as well as fatty infiltrates, which both may be detected by MRI 69 .…”
Section: Right Ventricular Functionmentioning
confidence: 99%
“…MRI is emerging as a useful "Arrhythmogenic Right Ventricular Cardiomyopathy/Dysplasia" non-invasive tool to identify morphologic abnormalities such as myocardial fat, right ventricular chamber size and shape, and wall motion abnormalities with newer cine techniques. However, with conventional MR technology, the identification of myocardial fat was not found to be a reliable predictor of the presence of ARVC/D 15 . Diffuse hypokinesis or regional wall motion abnormalities of the right ventricle can be seen with contrast ventriculography, considered to be the most reliable test to assess structural abnormalities.…”
Section: A) Structural Abnormalities and Pathophysiologymentioning
confidence: 84%
“…120 Yet, myocardial fibrosis and fat as potential diagnostic features were not integrated in the TFC, because of their limited specificity, high intra-and inter-observer variability and the need for highly specialised interpreters. 121,122 This owes to the fact that the RV is very thin and epicardial fat cannot reliably be distinguished from intramyocardial fat. However, CMR plays an important role for ARVC/D diagnosis (see Figure 2A).…”
Section: Cardiac Magnetic Resonance Tomographymentioning
confidence: 99%